2016
DOI: 10.1111/asj.12724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health status on fattening performance in young crossbred polish Holstein‐Friesian × Limousin Bulls and steers

Abstract: The aim of this study was to determine the effect of disease incidence on selected parameters of cattle fattening performance and carcass quality, and the fatty acid profile of beef. The experimental materials comprised 16 bulls and 16 steers, Polish Holstein-Friesian × Limousin crossbreeds (including 10 healthy and six treated animals of each category). At 5 weeks of age, bloodless castration was carried out using a rubber elastrator. The calves were fed milk replacer provided in automatic feeding stations. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although research investigating the role of the rumen microbiome in influencing feed efficiency phenotype exists, data are limited, especially for beef cattle. Furthermore, many of these studies are restricted to only investigating rumen liquid digesta and use alternate methods of measuring feed efficiency, such as feed conversion ratio (FCR), which can be problematic due to the unfavorable genetic correlations with between growth rate and mature body size ( Schenkel et al, 2004 ). This implies that selection of cattle for improved FCR will lead to an increase in mature body size and therefore, maintenance requirements ( Schenkel et al, 2004 ; Crews, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although research investigating the role of the rumen microbiome in influencing feed efficiency phenotype exists, data are limited, especially for beef cattle. Furthermore, many of these studies are restricted to only investigating rumen liquid digesta and use alternate methods of measuring feed efficiency, such as feed conversion ratio (FCR), which can be problematic due to the unfavorable genetic correlations with between growth rate and mature body size ( Schenkel et al, 2004 ). This implies that selection of cattle for improved FCR will lead to an increase in mature body size and therefore, maintenance requirements ( Schenkel et al, 2004 ; Crews, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many of these studies are restricted to only investigating rumen liquid digesta and use alternate methods of measuring feed efficiency, such as feed conversion ratio (FCR), which can be problematic due to the unfavorable genetic correlations with between growth rate and mature body size ( Schenkel et al, 2004 ). This implies that selection of cattle for improved FCR will lead to an increase in mature body size and therefore, maintenance requirements ( Schenkel et al, 2004 ; Crews, 2005 ). This has negative economic and environmental ramifications for beef production ( Arthur et al, 2001 ; Schenkel et al, 2004 ; Crews, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Osorio et al [ 43 ], ewes’ milk had a beneficial influence on the concentrations of n -3 fatty acids and the n -6/ n -3 PUFA ratio in the IMF of lamb meat, compared to milk replacer. Wielgosz et al [ 4 ] reported that diseases and infections during the rearing period negatively affected IMF composition in calves. In addition, in this experiment, diseases that occurred in the pre-weaning period might have influenced the post-weaning health status of calves and, consequently, the fatty acid profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, those machines are expensive and the group housing of calves is associated with an increased risk of disease transmission. Therefore, alternative calf rearing systems are being sought [ 4 ]. One of these alternatives is a foster cow system [ 5 ], where one cow usually nurses two calves, and unrestricted access to fresh milk affects beneficially in later fattening results and, ultimately, beef quality [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%